Optimalisasi Tata Kelola Jaringan dan Layanan untuk Mendorong Peningkatan Kualitas Infrastruktur Digital - Izayanti, Eva; Restu Alpiansyah (Insan Kreasi Media, 2024)
The sharia banking industry in Indonesia, including Bank NTB Syariah Mataram, is facing big challenges in strengthening digital infrastructure. This strategic step aims to improve operational efficiency and service quality to customers. Strengthened infrastructure, the bank is committed to maximizing financial services to better meet customer expectations. In this context, the author carries out the Community Service Program (KKN) at Bank NTB Syariah Mataram. The main focus of this activity is to apply the theoretical knowledge gained during lectures in practical situations, especially in terms of financial analysis and improving the financial reporting process. This entire series of activities was completed within one month. The author succeeded in making a significant contribution in efforts to increase the effectiveness of Bank NTB Syariah Mataram's financial reporting. The results of this KKN show that the integration between academic education and practical practice provides real benefits not only for the institution, but also for the students involved. KKN at Bank NTB Syariah Mataram broadens students' experience in the world of work, increases the application of theory in real situations, and positively contributes to the development of digital infrastructure. This activity implies that Bank NTB Syariah Mataram needs to continue to strengthen its digital infrastructure to remain relevant and competitive as it continues to develop.